Problematika Penegakkan HAM Ditinjau Dalam Segi Aspek Kemasyarakatan - Pedrico Yoel Batoean Sihite; Ananda Rafli Haritsah; Muhammad Auza Syam; Muhammad Prima Adiguna; Yudea Maruli Seraf; Fajar Muhammad; Mulyadi M (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
There is a lot of misunderstanding that every human right is considered a human right by both law enforcers and society who cannot distinguish between what is called a human right and what is not called a human right. Of the many cases of human rights violations that have occurred in Indonesia, from cases of human rights violations committed by the community against the community to law enforcement officials who have committed human rights violations or even implemented a law enforcement system that violates human rights. Human rights enforcement in Indonesia is still not implemented, due to the rampant acts of human rights violations. The lack of enforcement of human rights is marked by the uneven distribution of existing legal services, especially in remote areas. Human rights enforcement in Indonesia is also limited by policies and laws such as the ITE Law and the Terrorism Law which limit people's ability to express opinions and form associations. The formation of the new draft Criminal Code has a role in minimizing human rights violations, namely the human rights of defendants who are subject to death sentences because in the new draft Criminal Code, the death penalty does not mean that the accused is executed immediately after the verdict, but looks at the next 10 years if the defendant is seen to have a change for the better, so the death penalty defendant is reduced to life imprisonment. This certainly prioritizes human rights above all else, especially the right to the life of the defendant.